2015
DOI: 10.1186/s13045-015-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Stage, age, and EBV status impact outcomes of plasmablastic lymphoma patients: a clinicopathologic analysis of 61 patients

Abstract: BackgroundPlasmablastic lymphoma (PBL) is a rare aggressive neoplasm with lymphoid and plasmacytic differentiation that is commonly associated with immunodeficiency and an unfavorable prognosis. Clinicopathologic features have been largely derived from cases reports and small series with limited outcome analyses.Patients and methodsThe demographic, clinicopathologic features, and clinical outcomes of a cohort of 61 patients with PBL were reviewed and analyzed.ResultsPatients had a median age of 49 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
144
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 29 publications
15
144
0
1
Order By: Relevance
“…1 It commonly occurs in the context of human immunodeficiency virus (HIV) infection or in association with other contexts of immunodeficiency such as autoimmune diseases, organ transplantation and in the elderly; [2][3][4][5] few studies have identified PL in patients without immunodeficiency. 6,7 Neoplastic cells resemble immunoblasts or plasmablasts with a B-cell terminal differentiation phenotype and they mostly have a non-germinal center (GC)-B subtype profile. [2][3][4][5][6][7][8] These cells constitutively express the plasma cell antigen CD138 (syndecan-1) and often harbor immunoglobulin (Ig) chain restriction with no or weak expression of B-cell mature markers such as CD20, CD79a and PAX5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It commonly occurs in the context of human immunodeficiency virus (HIV) infection or in association with other contexts of immunodeficiency such as autoimmune diseases, organ transplantation and in the elderly; [2][3][4][5] few studies have identified PL in patients without immunodeficiency. 6,7 Neoplastic cells resemble immunoblasts or plasmablasts with a B-cell terminal differentiation phenotype and they mostly have a non-germinal center (GC)-B subtype profile. [2][3][4][5][6][7][8] These cells constitutively express the plasma cell antigen CD138 (syndecan-1) and often harbor immunoglobulin (Ig) chain restriction with no or weak expression of B-cell mature markers such as CD20, CD79a and PAX5.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Neoplastic cells resemble immunoblasts or plasmablasts with a B-cell terminal differentiation phenotype and they mostly have a non-germinal center (GC)-B subtype profile. [2][3][4][5][6][7][8] These cells constitutively express the plasma cell antigen CD138 (syndecan-1) and often harbor immunoglobulin (Ig) chain restriction with no or weak expression of B-cell mature markers such as CD20, CD79a and PAX5.…”
Section: Introductionmentioning
confidence: 99%
“…PBL commonly affects extranodal sites, predominantly the oral cavity, gastrointestinal tract and the skin Contrasting, in the present case, our patient is a female patient and had a more advanced age than most seropositive patients. The best prognosis is associated with younger patients, early stage of the disease and no lymph node involved [12].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmablastic lymphoma (PBL) is an aggressive B-cell malignancy, thought to be related to DLBCL, in which the lymphoma cells exhibit morphologic and immunophenotypic features of plasma cell differentiation [46] (Supporting Information Fig. 3).…”
Section: Plasmablastic Lymphomamentioning
confidence: 99%